Anatomical Study of the Portal Venous System - Hamid, Asadullah (Journal of Natural Sciences – Kabul University, 2025)
The liver is the largest gland in the body. Blood passes through the liver sinusoids and ultimately leaves the liver via the hepatic veins, which drain into the vena cava. The liver sinusoids remove bacteria and other particulate matter that may enter the blood from the gastrointestinal tract. The liver holds a unique position concerning the venous blood from the portal vein, which drains blood from the gastrointestinal tract through the liver before entering the general circulation. The portal vein is the primary afferent vessel and supplies most of the blood to the liver. The portal venous system is defined as one that begins and ends in capillaries. The name "portal vein" applies to the venous system that originates in the capillaries of the intestine and terminates in the hepatic sinusoids.